GAS5 regulated by FTO-mediated m6A modification suppresses cell proliferation via the IGF2BP2/QKI axis in breast cancer - Yuzhao Yan; Jing Ma; Qingqiu Chen; Ting Zhang; Rui Fan; Junze Du (Discover Oncology, 2024)
Abstract Background The lncRNA growth arrest-specific 5 (GAS5) is involved in regulating breast cancer progression. In this study, we aimed to elucidate the function and mechanism of GAS5 in breast cancer. Methods The expressions of GAS5, fat mass and obesity-associated protein (FTO), insulin-like growth factor 2 mRNA-binding protein 2 (IGF2BP2), and Quaking (QKI) were assessed by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and western blot. The m6A modification level of GAS5 was detected using m6A immunoprecipitation assay (MeRIP). The interaction between IGF2BP2 and GAS5 or QKI was detected using RNA immunoprecipitation assay (RIP) and dual luciferase reporter assay. Cell proliferation was measured using the Cell Counting Kit-8 (CCK-8) assay. The biological functions of the FTO/GAS5/IGF2BP2/QKI axis was assessed using the tumor xenograft assay. Results LncRNA GAS5 expression decreased in breast cancer and was regulated by FTO-mediated m6A modification in an IGF2BP2-dependent manner, resulting in decreased GAS5 stability and expression. GAS5 recruited IGF2BP2 to target QKI and upregulated QKI expression in breast cancer cells. GAS5 suppressed breast cancer growth via IGF2BP2/QKI, and this inhibitory effect was modulated by FTO both in vitro and in vivo. Conclusions GAS5 regulated by FTO-mediated m6A modification represses the growth of breast cancer via the IGF2BP2/QKI pathway, suggesting that the FTO/GAS5/IGF2BP2/QKI pathway can be a potential target for breast cancer treatment.